Malaysian older persons' perceptions about falls and their desired educational website characteristics: A qualitative study. - Cheah Ping Ng; Devinder Kaur Ajit Singh; Maw Pin Tan; Saravana Kumar (PLoS ONE, 2022)
Falls is a common and debilitating condition among the older population, intensifying the need to educate older persons about falls. Technology advancement enables effective and efficient delivery of falls education to the older population. However, there is paucity of information on the perception of Malaysian older population on falls and their preferred website characteristics such as font size, design, layout, colour, navigation, and use of graphics or videos. Physiological changes in vision, cognition and psychomotor skills can affect how the older persons use the website. As Malaysia is a multicultural country, the needs of the website characteristics and falls perception of older persons may differ greatly. The aim of this study was to explore the perceptions of the older persons about falls and their desired website characteristics. Twenty-five community-living older persons (n = 25) of age 60 years and above were involved in the focus group discussions. NvivoTM software was used for data management and thematic analysis was undertaken. Emerging themes included 'Perceptions of falls in older persons', 'Actions taken when falls occurred', 'Perceived prevention strategies for falls' and 'End user requirements for falls educational website'. Falls were perceived as both an avoidable and a non-avoidable incident. Although the participants mentioned physical activity and home hazard modifications as strategies to prevent falls, they mainly discussed self-initiated precautionary approaches in falls prevention. Regarding desired website characteristics, the participants emphasized on easily readable text, appealing design, clear information, use of images/videos, and simple website navigation. Special requirements for colour selection and multi-language options were also raised. The delivery of falls education through website can be made possible by understanding the perception of older persons about falls and their requirements for the website. This is especially important as ethnic and cultural influences may play a role on their perceptions about falls and desired website characteristics.